Molecular pathogenesis of megalencephalic leukoencephalopathy with subcortical cysts: mutations in MLC1 cause folding defects - Anna Duarri; Óscar Teijido; Tania López-Hernández; Gert C. Scheper; H. Barrière; Ilja Boor; Fernando Aguado; António Zorzano; Manuel Palacı́n; Albert Martı́nez; Gergely L. Lukács; Marjo S. van der Knaap; et al. (2008)
Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare type of leukodystrophy, most often caused by mutations in the MLC1 gene. MLC1 is an oligomeric plasma membrane (PM) protein of unknown function expressed mainly in glial cells and neurons. Most disease-causing missense mutations dramatically reduced the total and PM MLC1 expression levels in Xenopus oocytes and mammalian cells. The impaired expression of the mutants was verified in primary cultures of rat astrocytes, as well as human monocytes, cell types that endogenously express MLC1, demonstrating the relevance of the tissue culture models. Using a combination of biochemical, pharmacological and imaging methods, we also demonstrated that increased endoplasmatic reticulum-associated degradation and endo-lysosomal-associated degradation can contribute to the cell surface expression defect of the mutants. Based on these results, we suggest that MLC1 mutations reduce protein levels in vivo. Since the expression defect of the mutants could be rescued by exposing the mutant-protein expressing cells to low temperature and glycerol, a chemical chaperone, we propose that MLC belongs to the class of conformational diseases. Therefore, we suggest the use of pharmacological strategies that improve MLC1 expression to treat MLC patients.